Penerapan Metode Hypnoteaching untuk Meningkatkan Pengetahuan Siswa pada Mata Pelajaran Akidah Akhlak Siswa Kelas VIII - Ade Yulisna; Kamaliah; Syarifah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
The variable used to increase students' knowledge on the subject of moral aqidah, class VIII private MTs Al-Ikhlas Pangkalan Susu, is the hypnoteaching method. The subjects of this study were students of class VIII 1 private MTs al-Ikhlas, totaling 32 people. This research was conducted in two cycles, where each cycle consisted of four stages, namely planning, action, observation, and reflection. Using qualitative descriptive analysis techniques. Before doing the action research, starting with the pre-cycle stage, at this stage the researcher made observations about the results of the evaluation of the learning of the moral aqidah chapters of tawakkal, endeavor, gratitude, patience, and qona'ah. From the results of the data that the researchers got, it was known from the initial conditions that in class VIII there were problems, namely students were not able to understand and master the subject matter of moral aqidah and were unable to remember the material that had been taught. So that student learning outcomes are low and do not reach the KKM 75 set by the madrasa. In the pre-cycle implementation, the average score of students was 59,62 with a student's completeness score of 28,12%. Then the first cycle was carried out, from the class action research data that the researchers got, there was an increase in the average score in the first cycle, to 71,56 with a student completeness score of 62,5%, but there were still many students who had not reached the KKM. Continued to the second cycle of action, in this action there was an increase again, namely to 87,34 with a student completeness score of 87,5%. This shows that the hypnoteaching method that the researcher uses is able to increase students' knowledge on the subjects of aqidah morals of class VIII students, especially on the material of tawakal, endeavor, gratitude, patience, and qona'ah, although not yet 100%.